Implementasi Maqashid Syariah Dalam Pelaksanaan Corporate Social Responsibility Pada PT. Pegadaian Syariah Cabang Ar-Hakim Medan - Sutria Anisa (Yayasan Rahmat Islamiyah, 2023)
The objectives of this research are: (1) To find out the implementation of maqashid sharia in CSR at PT. Sharia Pawnshop Ar-Hakim Medan Branch. (2) To find out whether or not the five maqashid sharia concepts have been implemented in terms of protecting religion, soul, mind, lineage, and property through CSR at PT. Pegadaian Syariah Branch of Ar-Hakim Medan in accordance with Islamic Shari'a. (3) To find out the benefits obtained by CSR by implementing maqashid sharia from PT. Sharia Pawnshop Ar-Hakim Medan Branch. Where this type of research is qualitative data method obtained in this study can be obtained through observation/interview techniques and using primary and secondary data sources. The results obtained are the implementation of Corporate Social Responsibility (CSR) at the Syariah Pawnshop Ar-Hakim Medan Branch which is more focused on the construction of mosque facilities, given to the elderly, especially customers, and distributed to orphans.